Evaluation in early chidhood education and the pedagogy of relation and listening: documenting and reflecting on the educational experience - Jorgiana Ricardo Pereira; Fátima Sampaio Silva (Universidade Federal de Santa Catarina, 2019)
The objective of this essay is to foster the debate about evaluation in Early Childhood Education, as a practice of recording and monitoring children development which results in the production of specific documentation regarding their development and learning processes in the pre-school period. It presents reflections upon this theme, based on the Brazilian legislation related to evaluation in Early Childhood Education. Its theoretical framework is the Pedagogy of Relation and Listening, formulated by Loris Malaguzzi. In addition, to elucidate the concept of evaluation, it describes an evaluation experience developed in Child Development Center of the Federal University of Ceará.